The True Story of Yeti, the “Abominable” Heterochromatic Gene of Drosophila melanogaster - Prozzillo, Yuri; Delle Monache, Francesca; Ferreri, Diego; Cuticone, Stefano; Dimitri, Patrizio; Messina, Giovanni (Frontiers in Physiology, 2019)
The Drosophila Yeti gene (CG40218) was originally identified by recessive lethal mutation and subsequently mapped to the deep pericentromeric heterochromatin of chromosome 2. Functional studies have shown that Yeti encodes a 241 amino acid protein called YETI belonging to the evolutionarily conserved family of Bucentaur (BCNT) proteins and exhibiting a widespread distribution in animals and plants. Later studies have demonstrated that YETI protein: i) is able to bind both subunits of the microtubule-based motor kinesin-I; ii) is required for proper chromosome organization in both mitosis and meiosis divisions; and more recently iii) is a new subunit of dTip60 chromatin remodelling complex. To date, other functions of YETI counterparts in chicken (CENtromere Protein 29, CENP-29), mouse (Cranio Protein 27, CP27), zebrafish and human (Cranio-Facial Development Protein 1, CFDP1) have been reported in literature, but the fully understanding of the multifaceted molecular function of this protein family remains still unclear. In this review we comprehensively highlight recent work and provide a more extensive hypothesis suggesting a broader range of YETI protein functions in different cellular processes.